Correlates of tobacco product reuptake and relapse among youth and adults in the USA: findings from the PATH Study Waves 1–3 (2013–2016). (22nd April 2020) - Edwards, Kathryn C; Kasza, Karin A; Tang, Zhiqun; Stanton, Cassandra A; Sharma, Eva; Halenar, Michael J; Taylor, Kristie A; Donaldson, Elisabeth A; Hull, Lynn C; Bansal-Travers, Maansi; Limpert, Jean; Zandberg, Izabella; et al.
Abstract : Objective: This study examines sociodemographic and tobacco use correlates of reuptake and relapse to tobacco use across a variety of tobacco products (cigarettes, electronic nicotine delivery systems, cigars, hookah and smokeless tobacco) among the US population. Design: Data were drawn from the first three waves (2013–2016) of the Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal cohort study of US youth (ages 12–17) and adults (ages 18+). Reuptake (past 30-day use among previous tobacco users) and relapse (current use among former established users; adults only) were examined among previous users of at least one type of tobacco product at Wave 1 (W1) or Wave 2 (W2) (n=19 120 adults, n=3039 youth). Generalised estimating equations were used to evaluate the association between demographic and tobacco use characteristics at baseline, with reuptake/relapse at follow-up, over two 1-year periods (W1–W2 and W2–Wave 3). Results: Any tobacco product reuptake occurred in 7.8% of adult previous users and 30.3% of youth previous users. Correlates of any tobacco reuptake included being male, non-Hispanic black and bisexual in adults, but race and sexual orientation were not consistent findings in youth. Among recent former users, relapse rates were greater (32.9%). Shorter time since last use and greater levels of tobacco dependence showed the strongest association with any tobacco relapse. Discussion: Continued clinical and public health efforts to provide adults with tools to cope with tobacco dependence symptoms, especially within the first year or two after quitting, could help prevent relapse.